Analysis Of The Effect Of Influencer Attractiveness, Online Consumer Review, Social Media Advertisement, And Influencer Endorsement On Online Consumer Purchase Intention - Muhammad Ravi Pramananta Aufar; Erlita Ridanasti (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to identify and analyze the influence of Influencer Attractiveness, Online Consumer Review, Social Media Advertisement, and Influencer Endorsement on Online Consumer Purchase Intention. This study uses the object of the fashion brand Zaafer Indonesia which is a Muslim clothing brand specifically for men. This study uses a quantitative method using primary data, namely a questionnaire and obtained 200 research respondents. The data that was successfully collected was analyzed statistically using SPSS to test the validity, reliability, and research hypothesis. The findings of this study indicate that: 1) Influencer attractiveness, Online consumer Review, Social Media Advertisement, and Influencer endorsement have a positive and significant effect on Purchase intention partially, and 2) Other results show that all variables have a simultaneous effect on Purchase intention. The managerial implications of the results of this study for Zaafer Indonesia are that companies need to maximize influencer attractiveness, online consumer reviews, advertisements on social media, and influencer endorsements in an integrated manner to increase consumer purchase interest in their Muslim men's fashion products.